The Role of Information Technology for The Muslim Community - Kusen, Kusen (International Conference of Moslem Society, 2018)
In the 21st century, most societies have entered the era of modern information technology. No doubt advanced equipment such as computers, mobile phones, tablet PCs become a vital tool in daily life. Advanced equipment is facilitated by the Internet to function optimally. Muslim societies, especially in Indonesia, utilize the technology available by the internet and its devices for use in various purposes such as da'wah tools, Islamic practice activities and other general activities. They are able to perform faster and more efficiently with the device. Various websites and social media support activities of Muslim communities such as Islamic finder, MyQur'an.com, Ukhuwah.or.id and social media such as WhatsApp, Line and blackberry messenger facilitate the preachers, and the Muslim community, in general, to use it in accordance with its purpose.